Whose Home; Which Island?: Displacement and Identity in 'My Island Home' - Stratton, Jon (Department of Contemporary Music Studies, 2013)
'My Island Home' has become a well-known musical assertion of Australian identity. Written in 1985 by Neil Murray, the song originally described the situation of the lead singer of the predominantly Indigenous Warumpi Band, George Burarrwanga, who had moved from Elcho Island in Arnhem Land to Papunya, a community west of Alice Springs. The song was subsequently popularized to a mainstream, settler Australian audience in two versions released by Christine Anu, who sang a revised version which identified Australia itself as the island home at the Sydney Olympics Closing Ceremony in 2000. This article tracks the history of version of 'My Island Home' up to that by Tiddas which closes the film Radiance, released in 1998. The article argues that central to the growing popularity of 'My Island Home' among both Indigenous and settler Australians was the increasing recognition of land rights and, correspondingly, the anxieties this caused among the dominant population.